INTEGRATION OF AUTHENTIC LANGUAGE ENVIRONMENTAND TEACHING ENGLISH FOR SPECIFIC PURPOSESIN GOOGLE CLASSROOM - Chuksina, Oksana (Revista Inclusiones, 2020)
Learning activities can be integrated into an authentic language environment by means ofGoogle classroom platform. The main objective of the study is to analyzethe advantages of Google classroom for teaching English in technical higher institutions.The idea about creating a hyper textbook withgeneral and specific components for various specialties is suggested. Empirical study of implementation of Google applicationsfor language education at Moscow Aviation Institute is analyzed. The benefits of using open educational resources to meet the students’ learning and professional needs are explained.Different creative activities for collaborative and individual learning are described. Effective time-management of the lesson and better communication between the students and the teacher is achieved by means of this platform. The adequate change of activity will increase students’ productivity. Google classroom is recommended to organize English teaching inmulti-level groups with different learning styles. The results of this study indicated that individual learning trajectory helps to achieve better results during the English course at the University. This study seeks to contribute to the methodology of developing language skillswhile teaching English for specific purposes with ICT tools